'That would break the containment': the co-production of responsibility and safety-by-design in xenobiology. Issue 1 (2nd January 2021) - Aparicio, Alberto
ABSTRACT: Few studies of frameworks of Responsible Research and Innovation (RRI) have addressed the meanings and framings of responsibility in relation to scientific practice. Researchers in the emerging field of xenobiology aim to explore the non-natural biological world through the development of alternative genetic systems, promising the safety of these systems with built–in–safety features (biocontainment). This article argues that approaches to responsibility partly shape the research agenda of a xenobiology laboratory. Conceptions of responsibility are co-produced with an imagination of the public as expectant of safety, and whether users may modify technological artefacts. I suggest the term 'technologies of compliance' to reflect that safety and the acceptance of new technology is a priority in synthetic biology research and design. This study provides an account based on ethnographic and interview data of the association of responsibility with design principles, relevant for RRI frameworks that are aligned with scientific practice.